The impact of top-down listening strategies and bottom-up listening strategies instruction in the students’ listening performance. - Pérez Gómez, Jaime Roberto
The importance of listening in language learning has only been recognized relatively recently (Oxford, 1993), since the role of listening comprehension in language learning was takenfor granted, merited little research and hardly ever pedagogical attention. Although listening played an important role in audio-lingual methods, students only listened to repeat and developing a better pronunciation (Feyten,1991). However, in recent years there has been an increased focus on second language ability because of its perceived importance in language learning acquisition (Sadighi, 2006: 1). Language learning depends on listening since it provides the aural input that serves as the basis for language acquisition and enables learners to interact in spoken communication (Guo& Wills, 2003: 3). It has been recently discussed that listening is the fundamental skill for language acquisition. For it has been considered as the main vehicle through which people gain a large portion of their education (Bulletin, 2004). In fact, input hypothesis suggested that people acquire language by the linguistic information they hear (Krashen, 1985). In addition, the message understood and processed will serve for reinforcing output. Successively, while processing the information heard students compare and integrate their previous knowledge to the information acquired after listening. Afterwards, the processed information is retained for future use (Earway, 1984).